Green Deal for industry: A clear policy framework is more important than funding - Karsten Neuhoff; Olga Chiappinelli; Mats Kröger; Frederik Lettow; Jörn Richstein; Franziska Schütze; Jan Stede; Sun Xi (DIW Weekly Report, 2021)
The European Commission is facing the challenge and opportunity of implementing the Green Deal while simultaneously initiating the recovery of the economy following the coronavirus crisis. Investments in the basic materials industry's transition to climate neutrality play a central role in this, as the sector is responsible for 16 percent of the EU's CO2 emissions and is key to downstream value chains. While funding for investment opportunities is often discussed, what is needed above all for the transition is a clear policy framework that makes investments in climate-friendly technologies economically viable and ensures that companies actually implement the investments in the transition. The necessary infrastructure and institutions must then be provided in the meantime. For these measures to be implemented in a timely and coordinated manner, it is important to set targets for climate-neutral production at national and European levels and to anchor them in the National Energy and Climate Plans and in the EU governance structure.
Keywords: Q54; Q58; L61; L52; H12; 330; Green COVID-19 Recovery; Industrial Decarbonisation; Policy Package; EU Green Deal